Édito - Véronique Lemoine-Bresson; Julien de Miribel; Catherine Souplet (Recherches en Éducation)
The aim of this issue is to bring together contributions that question the places, roles and experiences of the actors in education. The eight articles are divided into two distinct but complementary groups. The first group invites to reflect on certain working modalities in collaborative research, by underlining that, nevertheless, their deployment is not without tensions and difficulties when it comes to the places and roles of each person. The second group proposes analyses that focus on the experiences of the actors and their effects in terms of professional development, transformation and learning. In both groups some of the virtues of collaboration between researchers in education have been showed, without falling into a form of angelism.